Rencana Tata Bangunan Lingkungan Kawasan Alam Hutan Pango-Pango Kecamatan Makale Selatan Kabupaten Tana Toraja - Astuti, Retno Fitri; Edy, Sarwo; Hetyorini, Hetyorini; Irawan, Chandra (Universitas Pelita Bangsa, 2020)
Pango-Pango Forest Area is a hilly area in Tana Toraja Regency, South Sulawesi Province. Currently, the Pango-Pango Forest area is used as a tourist area to enjoy nature and scenery. In addition, the area filled with pine forests is also developed by the surrounding residents as a plantation area, both horticulture, fruit and vegetables, coffee, and enau. But unfortunately, the condition of roads and facilities in this area is not adequate considering the roads in this area have just opened. Therefore, the development of land function in this area must be followed by the development of the condition of public facilities, social, and infrastructure, especially the Pango-Pango Forest tourist area began to be crowded by the public. The existing buildings in the Pango-Pango Forest area are also still very minimal, and are dominated by semi-permanent buildings owned by residents that are used for sales. For future development, this area needs to be regulated so that the emergence of new buildings supporting tourism does not interfere with the existing natural conditions and disrupt the view that is the main attraction of this tourist area. This RTBL activity in addition to organizing tourist areas also organizes areas that can be used by residents as commercial areas. This commercial area is an area where residents sell the produce of this area's plantations